Task based activities to develop vocabulary in children - Sánchez B., Carolina
This project has been developed to determine importance of the use of task-based activities to develop vocabulary in children. Task-based activities have been defined as tasks that necessarily need a communication goal, so when the students use these kind of tasks, they have to work to communicate each other in order to complete the task. Task-based activities involve students? interaction and it is due to the interaction between them that facilitate language acquisition. Through the use of task-based activities, students are pushed to use the target language since tasks-based activities involve learners in a different mental process because they have to express their feelings, thoughts, or ideas. Also, task-based activities remove teacher domination, and students get chance to participate in class, to open and close conversations, to interact naturally, to interrupt and challenge. As with the use of task-based activities the learners have to use the target language, they can develop their vocabulary and fluency simultaneously. Without doubt, task based activities are the best teacher`s tool to develop vocabulary on his/her students.